2015
DOI: 10.5468/ogs.2015.58.5.346
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cesarean section after induced versus spontaneous labor at term gestation

Abstract: ObjectiveTo investigate whether the cesarean section (CS) rate is increased in women whose labor was induced compared to those who had spontaneous labor at term pregnancy. MethodsA retrospective study was performed in women whose labor was either induced (induction group, n=497) or spontaneous (spontaneous group, n=878) at 37+0 to 41+6 weeks of gestation from January 2008 to June 2009. Maternal age, parity, body mass index (BMI), Bishop scores, gestational age, hypertension, diabetes, delivery mode, indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
2
15
2
2
Order By: Relevance
“…On the other hand, induction did not increase the risk of surgical delivery in multiparous women according to our results. Lee et al (9) proposed that the rate of C-section was associated with the Bishop score but not impacted by labor induction; this is consistent with to our results. As a result, there is no certainty that induction increases the risk for C-section.…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, induction did not increase the risk of surgical delivery in multiparous women according to our results. Lee et al (9) proposed that the rate of C-section was associated with the Bishop score but not impacted by labor induction; this is consistent with to our results. As a result, there is no certainty that induction increases the risk for C-section.…”
Section: Discussionsupporting
confidence: 83%
“…13 Conversely, Lee et al reported that AMA, BMI, lower Bishop score, primiparity, but not induction of labor, significantly increased the rate of eCS according to multivariate analysis. 26 However, their results are inconsistent with ours because Lee et al's study considered both older and younger women. Our results showed that induction of labor in older nulliparous women at term was an independent predictive factor for intrapartum eCS.…”
Section: Discussioncontrasting
confidence: 65%
“…Previous studies analyzing the risk factors for eCS have revealed birth weight > 4000 g and maternal obesity as significant factors aside from maternal age and labor induction, similar to our results. 13,26 Moreover, these factors would be affected by body weight gain and increased prevalence of DM and GDM as a result of aging. 7,9 The presence of uterine myoma has also been associated with myometrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that degree of cervical ripening, higher gestational age, multi-parity, and lower maternal age are correlated with success of VD, though these studies mostly focused on term pregnancy [215161718]. Indeed, few reports to date have evaluated the predictive factors for labor induction success at preterm gestation.…”
Section: Discussionmentioning
confidence: 99%